2004
DOI: 10.1177/0148607104028004224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L‐arginine infusion during ischemia on gut blood perfusion, oxygen tension, and circulating myeloid cell activation in a murine gut ischemia/reperfusion model

Abstract: ARG infusion improves intestinal blood perfusion during ischemia but primes and activates circulating myeloid cells excessively. Consequently, i.v. infusion of ARG during ischemia reduces survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 17 publications
(35 reference statements)
0
22
0
Order By: Relevance
“…Since half of GLN mice died within several hours after 75 min of ischemia, we examined these parameters in the 50 min ischemia model. Because our previous study revealed circulating myeloid cell priming and activation to be prominent at 4 h after reperfusion, we killed the mice at this time point in the present study [5,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since half of GLN mice died within several hours after 75 min of ischemia, we examined these parameters in the 50 min ischemia model. Because our previous study revealed circulating myeloid cell priming and activation to be prominent at 4 h after reperfusion, we killed the mice at this time point in the present study [5,11].…”
Section: Discussionmentioning
confidence: 99%
“…Since L-arginine enhances leukocyte function and nitric oxide production, provision of L-arginine to patients with preexisting excessive leukocyte activation is controversial [11,[15][16][17][18]. On the other hand, GLN treatment has been considered to be safe in critically ill or septic patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…NO exerts beneficial effects, such as vasodilation and protecting vascular integrity. There are studies supporting that NO ameliorates mucosal injury after I/R (Fukatsu et al, 2004;Horie et al, 1998;Sayan et al, 2008) and lung injury caused by intestinal ischemia (Terada et al, 1996). Additionally, nitrite use for cardiovascular disease therapy is under investigation (Galvert and Lefer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…L-arginine is the substrate for nitric oxide synthase (NOS), and its administration seems to be beneficial in preventing I/R injury, which reflects the possible protective role of NO. There are also controversial reports demonstrating that this molecule is cytotoxic and needs to be further investigated (Fukatsu et al, 2004). NO protects vessels by acting as a vasodilator, an anti-inflammatory agent, an inhibitor of neutrophil adherence and a scavenger of OFR (Emre et al, 2008;Horie et al, 1998;Kubes and McCafferty, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The visible effects of small bowel injuries induced by IR range from the loss of villi to the presence of an extended subepithelial space. Recent evidence indicates that arginine may improve intestinal recovery and accelerate the repair of intestinal mucosa following IR [32], possibly by increasing mucosal mass, villus height, crypt depth, and the thickness of bowel wall. In this study, arginine supplementation increased the mucosal DNA content of the proximal jejunum in animals with intestinal IR (Fig.…”
Section: Power Calculationmentioning
confidence: 99%